Speed of cooling after cardiac arrest in relation to the intervention effect: a sub-study from the TTM2-trial - Rupert F. G. Simpson; Josef Dankiewicz; Grigoris V. Karamasis; Paolo Pelosi; Matthias Haenggi; Paul J. Young; Janus Christian Jakobsen; Jonathan Bannard-Smith; Pedro D. Wendel-Garcia; Fabio Silvio Taccone; Per Nordberg; Matt P. Wise; et al. (Critical Care, 2022)
Abstract Background Targeted temperature management (TTM) is recommended following cardiac arrest; however, time to target temperature varies in clinical practice. We hypothesised the effects of a target temperature of 33 °C when compared to normothermia would differ based on average time to hypothermia and those patients achieving hypothermia fastest would have more favorable outcomes. Methods In this post-hoc analysis of the TTM-2 trial, patients after out of hospital cardiac arrest were randomized to targeted hypothermia (33 °C), followed by controlled re-warming, or normothermia with early treatment of fever (body temperature, ≥ 37.8 °C). The average temperature at 4 h (240 min) after return of spontaneous circulation (ROSC) was calculated for participating sites. Primary outcome was death from any cause at 6 months. Secondary outcome was poor functional outcome at 6 months (score of 4–6 on modified Rankin scale). Results A total of 1592 participants were evaluated for the primary outcome. We found no evidence of heterogeneity of intervention effect based on the average time to target temperature on mortality (p = 0.17). Of patients allocated to hypothermia at the fastest sites, 71 of 145 (49%) had died compared to 68 of 148 (46%) of the normothermia group (relative risk with hypothermia, 1.07; 95% confidence interval 0.84–1.36). Poor functional outcome was reported in 74/144 (51%) patients in the hypothermia group, and 75/147 (51%) patients in the normothermia group (relative risk with hypothermia 1.01 (95% CI 0.80–1.26). Conclusions Using a hospital’s average time to hypothermia did not significantly alter the effect of TTM of 33 °C compared to normothermia and early treatment of fever.